2020
DOI: 10.2337/dc19-1943
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Clinical Characteristics and Prescribing Preferences for SGLT2 Inhibitors and GLP-1 Receptor Agonists, 2013–2018

Abstract: There is a paucity of data evaluating recent changes in clinical and prescriber characteristics of patients initiating sodium-glucose cotransporter 2 inhibitors (SGLT2i) and glucagon-like peptide 1 receptor agonists (GLP-1RA). RESEARCH DESIGN AND METHODS U.S.-based administrative claims data (July 2013 to June 2018) were used to identify initiators of SGLT2i and GLP-1RA. RESULTSOver 5 years, empagliflozin initiation (as a proportion of SGLT2i) increased by 57.1% (P < 0.001 for trend), while canagliflozin initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 9 publications
5
65
0
Order By: Relevance
“…Arnold et al reported the real‐world use of SGLT2 inhibitors and GLP analogues to be 5.2% and 6.0%, respectively, among a study population eligible for participation in the EMPAREG or LEADER trial 34 and similar proportions of cardioprotective GLD users were reported by others 20,23 . Among initiators of cardioprotective GLDs in the period 2013 to 2018, three recent studies observed a relatively stable prevalence of patients with T2DM and CVD, although in the context of absolute increases in cardioprotective GLD use in the same time period 21,22,24 …”
Section: Discussionmentioning
confidence: 81%
“…Arnold et al reported the real‐world use of SGLT2 inhibitors and GLP analogues to be 5.2% and 6.0%, respectively, among a study population eligible for participation in the EMPAREG or LEADER trial 34 and similar proportions of cardioprotective GLD users were reported by others 20,23 . Among initiators of cardioprotective GLDs in the period 2013 to 2018, three recent studies observed a relatively stable prevalence of patients with T2DM and CVD, although in the context of absolute increases in cardioprotective GLD use in the same time period 21,22,24 …”
Section: Discussionmentioning
confidence: 81%
“…In addition, the side effect profile of pioglitazone including risk of fluid retention and HF makes it difficult to choose pioglitazone as a first-line agent over metformin [92] There has been an immense proliferation in the evidence suggesting the beneficial cardio-protective effects of SGLT2i and GLP-1RA especially in the last 5 years. Despite all this, the uptake of these medications outside of diabetologists domain remains low [93,94]. It is crucial to avoid therapeutic inertia [95] and therapy beyond metformin is escalated in a timely manner.…”
Section: Thiazolidinediones (Tzds)mentioning
confidence: 99%
“…However, many individuals with the condition are not prescribed these modern and cost-effective therapies, particularly GLP-1 receptor agonists that require injection. 6 Important barriers include: expertise in the use of these newer agents residing mainly in secondary care (the majority of people with type 2 diabetes are cared for in primary care); downward pressure on cost; and inadequate coordination between primary and secondary care. Although there are examples of good practice, including diabetes-focused locally enhanced services, many individuals only receive input from secondary care once they have had the condition for many years and/or have developed complications (e.g.…”
Section: Effective Treatment To Prevent Complicationsmentioning
confidence: 99%
“…Two new drug classes (GLP‐1 receptor agonists, SGLT2 inhibitors) for the first time reliably reduce weight and prevent heart disease and stroke. However, many individuals with the condition are not prescribed these modern and cost‐effective therapies, particularly GLP‐1 receptor agonists that require injection 6 . Important barriers include: expertise in the use of these newer agents residing mainly in secondary care (the majority of people with type 2 diabetes are cared for in primary care); downward pressure on cost; and inadequate coordination between primary and secondary care.…”
Section: What Change Is Needed?mentioning
confidence: 99%